Cupcakes and beefcakes: students' readings of gender in superhero texts. Issue 1 (2nd January 2021) - Dallacqua, Ashley K.; Low, David E.
ABSTRACT: Given the growing interest and representation of superheroes in comics and other media, we are interested in the ways young people read superhero texts and how those readings influence their conceptualisations of gender within and outside educational spaces. In this article we explore students' responses to (re)presentations of gender in superhero texts (which include graphic novels, comic books, films, YouTube, and more), and examine how they reproduce and/or challenge assumptions about gender identity. This ethnographic study focuses on six seventh-graders across a school year in the United States. Our findings suggest that (1) students employ superhero texts as a multimedia resource for inquiring into gender, (2) superhero texts contribute to students' complex and evolving understandings of gender, and (3) students both critique and reify gender ideologies that are surfaced through their transactions with comics and related media.